Sequence-tagged sites of cDNA clones in Solanum tuberosum and their evaluation as molecular markers in Solanaceae species - Liebenberg, Junita (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.